Neurosurgical management of head injuries incurred during sports: a single centre experience. (3rd March 2020) - Hall, Samuel; McElligott, Simon; Sadek, Ahmed-Ramadan; Griffith, Colin; Waters, Ryan; Nader-Sepahi, Ali
Abstract: Introduction: Accidents during sporting activities are a common cause of head injury, particularly in children and young adults. Whilst most sporting head injuries are minor, there remains a proportion which is associated with high morbidity and mortality. The epidemiology of sports associated head injuries is variable based on geographical region so the aim of this study was to review the management and outcomes of sporting head injuries managed by a single neurosurgical unit in the South of England. Method: A retrospective review of the Trauma Audit and Research Network database was conducted for all patients admitted to a tertiary neurosurgical centre over a six-year period (January 2011–December 2016). Case notes were reviewed for demographics, mechanism of injury, injury severity score, intensive care admission, surgical interventions and Glasgow Outcome Score at discharge. Results: Seventy-six patients (mean age: 37.6 ± 18.4 years, male gender n  = 43; 56.6%) were eligible for inclusion in this series. Horse riding accidents were identified as the most common cause of head injury ( n  = 31; 40.8%). Fifteen patients (19.7%) in this series had a severe head injury (GCS 3–8 on admission). Twenty-eight (36.8%) patients required admission to an intensive care unit and 26 (34.2%) patients underwent neurosurgical intervention. At discharge, 68 (89.5%) patients had a Glasgow Outcome Score 4–5. Conclusion: The majority of patients with head injuries admitted to a neurosurgical unit can expect a good functional outcome despite the need for intensive care or neurosurgical intervention. The range of sports resulting in head injury is likely influenced by geographic location; however, further national study is required for wider comparison.